THE ROLE OF FOKLORE RIAU IN DEVELOPMENT OF CHILDREN'S LANGUAGE BEHAVIOR IN TK PEMBINA NEGERI ROKAN HULU (PERAN CERITA RAKYAT RIAU DALAM PERKEMBANGAN PERILAKU BAHASA ANAK DI TK PEMBINA NEGERI KABUPATEN ROKAN HULU) - Putri, Delia (Universitas PGRI Sumatera Barat, 2018)
This study aims to describe the role of Riau folklore in the development of children's language behavior in TK Pembina Negeri of Rokan Hulu Regency, Riau Province. The results of the study show that Riau folklore is very important to be applied, one of which is to preserve regional culture to the younger generation. In addition, Riau folklore can help develop children's language behavior. Children who are classified as active tend to respond verbally while children who are classified as passive tend to give nonverbal responses. Stimulus can also be given to children, which can be in the form of singing, praise, and reward. Children's language behavior can develop well because it uses various methods or techniques in the application of folklore, including using audio-visual media, image media, and hand puppets.